The direct employment impact of public investment - Moszoro, Marian (International Monetary Fund, 2021)
We evaluate the direct employment effect of the public investment in key infrastructure-electricity, roads, schools and hospitals, and water and sanitation. Using rich firm-level panel data from 41 countries over 19 years, we estimate that USD 1 million of public spending in infrastructure create 3-7 jobs in advanced economies, 10-17 jobs in emerging market economies, and 16-30 jobs in low-income developing countries. As a comparison, USD 1 million public spending on R and D yields 5-11 jobs in R and D in OECD countries. Green investment and investment with a larger R and D component deliver higher employment effect. Overall, we estimate that one percent of global GDP in public investment can create more than seven million jobs worldwide through its direct employment effects alone
10.5089/9781513573793.001
Keywords: Graue Literatur; Crisis; Public Investment; Infrastructure; Stimulus; COVID; Recovery; National Government Expenditures and Related Policies; Employment; Foreign Exchange; Informal Economy; Other Public Investment and Capital Stock; Underground Econom; Economics: General; National Government Expenditures and Related Policies: Infrastructures; Public Finance; Unemployment; Wages; Intergenerational Income Distribution; Aggregate Human Capital; Aggregate Labor Productivity; Labor Economics: General; Labor Demand; Aggregate Factor Income Distribution; Economic & financial crises & disasters; Economics of specific sectors; Labour; income economics; Public finance & taxation; Macroeconomics; Public investment spending; Expenditure; Labor; National accounts; Currency crises; Informal sector; Economics; Public investments; Employment; Economic theory; Labor economics; Job creation; Income